Ischemic stroke can have a T1w hyperintense appearance in absence of intralesional hemorrhage - Weston, Philippa; Behr, Sebastien; Garosi, Laurent; Maeso, Christian; Carrera, Ines (Frontiers in Veterinary Science, 2022)
Magnetic Resonance Imaging (MRI) signal changes associated with ischemic stroke are typically described as T2w and FLAIR hyperintense, and T1w isointense lesions. Intralesional T1w hyperintensity is generally attributed to either a hemorrhagic stroke, or an ischemic stroke with a with hemorrhagic transition, and has an associated signal void on gradient echo (GE) sequences. Cases of ischemic stroke with T1w hyperintense signal in absence of associated signal void on GE sequences have been sporadically demonstrated in human stroke patients, as well as in dogs with experimentally induced ischemia of the middle cerebral artery. This multicenter retrospective descriptive study investigates the presence of T1w hyperintensity in canine stroke without associated signal void on GE sequences. High field (1.5Tesla) MRI studies of 12 dogs with clinical presentation, MRI features and cerebrospinal fluid results suggestive of non-hemorrhagic CVA were assessed. The time between observed onset of clinical signs and MRI assessment was recorded. All 12 patients had an intralesional T1w hyperintense signal compared to grey and white matter, and absence of signal void on T2*w GE or SWI sequences. Intralesional T1w hyperintensities were either homogenously distributed throughout the entire lesion (6/12), or had a rim-like peripheral distribution (6/12). The mean time between recorded onset of clinical signs and MRI assessment was 3 days, however the age range of lesions with T1w hyperintense signal observed was 1- 21days, suggesting that such signal intensities can be observed in acute, subacute or chronic stages of ischemic stroke. Follow up was recorded for 7/12 cases, all of which showed evidence of neurological improvement whilst in hospital, and survived to discharge. Correlation of the age and MRI appearance of lesions in this study with similar lesions observed in human and experimental studies suggests that these T1w hyperintensities are likely caused by partial tissue infarction or selective neuronal necrosis, providing an alternative differential for these T1w hyperintensities observed.